MARE-WINT: New Materials and Reliability in Offshore Wind Turbine Technology - Ostachowicz, Wiesław; McGugan, Malcolm; Schröder-Hinrichs, Jens-Uwe; Luczak, Marcin (Springer Nature, 2016)
renewable; green; energy; environment; law; policy